Analisis Volatilitas Harga Bitcoin Setelah Halving Terhadap Harga Ethereum, Tether, Binance Coin, dan USDC - Darmawan, Surya; Azizah, Wafiq (Sains: Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze Bitcoin price volatility after halving by considering interactions with Ethereum, Tether, Binance Coin, and USD Coin. This research was conducted because Bitcoin halving is a significant event affecting the dynamics of the crypto market, but its impact on price volatility is not fully understood. This research uses the EGARCH (Exponential Generalized Autoregressive Conditional Heteroskedasticity) method with purposive sampling technique. Daily price data from Bitcoin, Ethereum, Tether, Binance Coin, and USD Coin in the period May 11, 2020 to May 31, 2024. The analysis results show that Bitcoin price volatility increased significantly after the halving event. In addition, there is an effect of Bitcoin price volatility after halving, namely on the price of Ethereum, Tether and Binance Coin. While the price of USD Coin cannot be proven because the daily closing price data is homoskedasticity.